PERANCANGAN GAME EDUKASI PENGEMBANGAN KEMAMPUAN LOGIKA BERBASIS ANDROID - Nirwana, Ira; Karnadi, Very (LPPM Universitas Putera Batam, 2021)
The development of this education game is based on the low interest of children in teaching and learning activities and the high level of addiction towards game that causes logical ability is not well-trained. The purpose of this research is to develop one’s logical ability, especially children with a quiz game. The method to collect the data is through interview and observation. The making of this game design uses Multimedia Development Life Cycle (MDLC) method that includes 6 steps, which are Concept, Design, Material Collecting, Assembly, Testing, and Distribution. But in this research, researcher limits it to the Testing step only. There’s also the usage of Unified Modeling language (UML) to describe how the game works that consists of 4 types of diagram, which are Use Case Diagram, Activity Diagram, Sequence Diagram, and Class Diagram. In this research, researcher uses a tool or software called Construct 2 to design the game. The result of the testng of this game is the game can be installed in Android device and can be stated as an user friendly application.